Pollen data obtained along the core MD-1 in florida mangrove diebacks - Cohen, Marcelo Cancela Lisboa (In: Cohen, MCL (2024): Florida mangrove diebacks [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.964591, 2024)
Sediments (1-cm3) were subsampled at 2 cm and 5 cm intervals along the 0 - 32 cm and 32 – 68 cm depth, respectively. Pollen and spore classification, with at least 300 pollen grains identified for each sample, was based on reference collections of the LSU Global Paleoecology Laboratory and Laboratory of Coastal Dynamics – UFPA, 14C Laboratory of the Center for Nuclear Energy in Agriculture (CENA/USP).